Workplace Drug Testing As A Drug Prevention Strategy for Public Transport Drivers: A Cross-sectional Study - Özşeker, Pınar Efeoğlu (The Bulletin of Legal Medicine, 2024)
Objective: Workplace drug testing for public transport drivers is required to apply or renew their driver’s certificate as well as a psychological evaluation according to the decision taken by the Adana Municipality Transportation Coordination Center in May 2015. In the context of this study, our objective is to safeguard both the rights of public transportation drivers who have tested positive for illicit substances and the safety of passengers. To this end, we aimed to corroborate the presence of these substances in urine or hair samples through liquid chromatography/ tandem mass spectrometry and to provide a nuanced interpretation of the results.Methods: The sample of the study consisted of 35 drivers who applied to the Forensic Toxicology Laboratory of Çukurova University, Department of Forensic Medicine, for confirmation analysis between January 2019 and December 2022. Opioids, cocaine, marijuana, amphetamines and their derivatives, benzodiazepine, buprenorphine, and synthetic cannabinoids were confirmed by liquid chromatography/tandem mass spectrometry in the urine or hair samples of 35 drivers.Results: All of 35 public transport drivers were male in this study and the mean age was 48.8±9.1 years old. The most detected substance in urine by immunoassay test were benzodiazepine, amphetamine and opiate, respectively. However, 91.5% of drivers showed false positive results in confirmatory methods. Benzodiazepine was detected in only 5% by liquid chromatography/tandem mass spectrometry while more than half of the 35 samples were positive for benzodiazepine in screening test.Conclusion: Immunoassay tests are susceptible to generating false positive results due to the cross-reactivity of analytes.
Keywords: workplace; drug testing; urine; hair